2021
DOI: 10.1007/s10049-021-00895-9
|View full text |Cite
|
Sign up to set email alerts
|

Alters- und geschlechtsbezogene Verteilung von Zuführung, Ersteinschätzung, Entlassart und Verweildauer in der zentralen Notaufnahme

Abstract: Zusammenfassung Einleitung Jährlich stellen sich bundesweit zahlreiche Patienten in zentralen Notaufnahmen vor. Ziel der vorliegenden Untersuchung war es, alters- und geschlechtsabhängig Zuführung, Ersteinschätzung, Entlassart und Verweildauer an einem universitären Standort zu analysieren. Material und Methodik In dieser retrospektiven Studie wurden alle Patientenkontakte der zentralen Notaufnahme des Universitätsklinikums Düsseldorf des Jah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
2
1
0
5
Order By: Relevance
“…Totally, 10.6% (40/378) of included patients were examined at and treated by other departments. When comparing the data from this study with data from a study focusing on patient characteristics in an ED of a German university hospital over the period of a year in 2019, we could see that the mean age of their patient population was 47 (SD 24; median 47, range 0-106) years, which was similar to that reported in this study (mean 46, SD 17.54 years; range 18-94 years) [ 33 ]. This study reported fewer female patients (162/377, 43%) than the previous study (48%).…”
Section: Resultssupporting
confidence: 78%
“…Totally, 10.6% (40/378) of included patients were examined at and treated by other departments. When comparing the data from this study with data from a study focusing on patient characteristics in an ED of a German university hospital over the period of a year in 2019, we could see that the mean age of their patient population was 47 (SD 24; median 47, range 0-106) years, which was similar to that reported in this study (mean 46, SD 17.54 years; range 18-94 years) [ 33 ]. This study reported fewer female patients (162/377, 43%) than the previous study (48%).…”
Section: Resultssupporting
confidence: 78%
“…Aktuell sind ca. 24 % [1] der Patienten in deutschen Notaufnahmen über 70 Jahre alt. Diese werden im Gegensatz zu Jüngeren häufiger mit dem Rettungsdienst eingeliefert, häufiger stationär aufgenommen und haben eine längere Verweildauer.…”
Section: Stand Der Dingeunclassified
“…Ab dem 60. Lebensjahr steigt zudem die in der Triage ermittelte Behandlungsdringlichkeit [1]. Komplexe Behandlungssituationen, atypische, abgeschwächte oder fehlende Symptomatik und Vorstellungsgründe im Rahmen geriatrischer Syndrome sind häufig, insbesondere bei Patienten mit Frailty.…”
Section: Stand Der Dingeunclassified
“…Ein Großteil der Patienten in einer Notaufnahme sind geriatrische Patienten, was einerseits mit der demografischen Entwicklung und andererseits mit steigender Morbidität im Alter zu erklären ist [23]. Durch die Begleiterkrankungen können Pharmakokinetik und das Nebenwirkungsrisiko der Analgetika erhöht sein.…”
Section: Geriatrische Patientenunclassified